Managing yourself : competence approach to personal development - Green, George; Candy, Anita; Colinns, Michael; Cartwright, Roger (Malden, Mass. : Blackwell, 1998)
The scenario. Where am I now? Where am I now? Where do I want to get to, and how am I going to get there? Who is going with me, what do I need and who can help?...
Keywords: Management; Psychology; Supervisors; Excutives; Supervisors -- Psychology; Executive ability; Self-management (Psychology)